Mauritius : Statistical Annex. (IMF Staff Country Reports; Country Report ;, 2001)
This report provides details of the IMF's projections and estimates for Mauritius on GDP at constant 1992 prices and at current prices by industrial origin; expenditure on GDP at constant 1992 and at current prices; sugar cultivation, yields, and output; electricity production and consumption; estimated labor force and employment, 1996-2000; summary of government finances; revenue and grants, budgetary central government; balance of payments; financing of central government deficits during 1995/96-1999/2000; summary accounts of the Bank of Mauritius and commercial banks, 1996-2000; summary of the tax system, 2000, and so on.